2021
DOI: 10.1080/14787210.2022.2000861
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of sofosbuvir-based antivirals in patients with COVID-19: a systematic review and meta-analysis of randomized trials

Abstract: BackgroundFew randomized trials evaluated the effect of combination therapy of Sofosbuvir-based direct-acting antivirals on mortality risk in patients with COVID-19. Therefore, we aimed to summarize the overall evidence in the form of a systematic review and meta-analysis. MethodsA systematic literature search with no language restriction was performed in electronic databases and preprint repositories to identify eligible randomized trials published up to July 8, 2021. A random-effects model was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, interpretations are limited by small sample size and lack of adjustment for the presence of cirrhosis. The repurposing of DAA therapy for use against COVID-19 has been investigated but results remain contentious (discussed below) [ [100] , [101] , [102] ].
EASL position Patients with chronic viral hepatitis (HBV or HCV) without cirrhosis do not appear to have an increased risk of SARS-CoV-2 infection or COVID-19 related mortality.
…”
Section: Risk Stratification and Disease Course Of Sars-cov-2 Infecti...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, interpretations are limited by small sample size and lack of adjustment for the presence of cirrhosis. The repurposing of DAA therapy for use against COVID-19 has been investigated but results remain contentious (discussed below) [ [100] , [101] , [102] ].
EASL position Patients with chronic viral hepatitis (HBV or HCV) without cirrhosis do not appear to have an increased risk of SARS-CoV-2 infection or COVID-19 related mortality.
…”
Section: Risk Stratification and Disease Course Of Sars-cov-2 Infecti...mentioning
confidence: 99%
“…There are no reported concerns about DAA therapy in patients with COVID-19. Small clinical studies and one meta-analysis initially suggested that sofosbuvir-based therapies may even have clinical benefit in the case of COVID-19 [ 102 ], although this has not been replicated in other systematic analyses [ 101 ].
EASL position Following SARS-CoV-2 infection, planned initiation of DAA therapy can be postponed until after COVID-19 has resolved.
…”
Section: Treatment Of Covid-19 In Patients With Chronic Liver Disease...mentioning
confidence: 99%
See 1 more Smart Citation
“… 312 However, according to a meta-analysis by Kow et al, sofosbuvir-based direct-acting antiviral agents have no protective effects against the development of severe illness in patients with COVID-19 with the current dosing regimen. 313 In a previous study, sofosbuvir demonstrated higher anti-viral efficiency against West Nile virus in hepatic cells than in lung cells. 314 This liver-targeting characteristic of sofosbuvir raises concerns for its use in treating SARS-CoV-2.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 91%
“…Further development of safe and reliable treatment strategies for people who fall ill is thus required for full and concerted pandemic response. Much effort has been devoted to designing [14][15][16][17][18] or repurposing [19,20] drugs for SARS-CoV-2 targets, but such pursuits have not yet produced breakthrough success. Such disappointment is not surprising, given the historical challenges of developing antiviral therapeutics [21], but it is imperative to persevere and to innovate.…”
Section: Introductionmentioning
confidence: 99%